Effect of prebiotic and probiotic supplementation on reduced pain in patients with fibromyalgia syndrome: a double-blind, placebo-controlled randomized clinical trial - CIn, Nazli Nur Aslan; Acik, Murat; TertemIz, Oktay Faysal; Aktan, Cile; Akcali, Didem Tuba; Cakiroglu, Funda Pinar; OzcelIk, Ayse Ozfer (Routledge Journals, Taylor & Francis Ltd, 2024)
It has recently been observed that microorganisms in the gut can regulate brain processes through the gut microbiota-brain axis, affecting pain, depression, and sleep quality. Consequently, prebiotics and probiotics may potentially improve physical, psychological, and cognitive states in those with fibromyalgia syndrome (FMS) who have an altered microbiota balance. In a randomised, double-blind, placebo-controlled clinical trial to determine the effects of probiotic and prebiotic treatments on pain, sleep, quality of life, and psychological distress (depression and anxiety) in FMS, 53 female participants with FMS were randomised to receive either: 1) 4 x 10(10) CFUs per day for the 18 patients in the probiotics group; 2) 10 g dose inulin per day for the 17 patients in the prebiotic group; or 3) a placebo for 8 weeks for the 18 patients in this group. The mean ages of the groups were similar and there was no significant difference between the groups. The impact of FMS on pain, sleep quality, quality of life, anxiety, and depressive symptoms were measured at baseline, 4 weeks, and 8 weeks post-intervention. Probiotic supplementation significantly decreased the Beck Depression Index (BDI), Beck Anxiety Index (BAI), and Pittsburgh Sleep Quality Index (PSQI) scores compared to baseline, while prebiotic supplementation only significantly decreased PSQI scores. Moreover, participants who received probiotic treatment presented a significantly reduced Visual Analogue Scale (VAS) score compared with those who received placebo treatment, after the interventions. Probiotic supplementation significantly improved sleep quality, depression, anxiety, and pain scores compared to those at baseline in FMS patients, while prebiotic supplementation significantly improved pain scores and sleep quality. The potential benefits of using probiotics for treatment management in FMS patients is supported by the results of the current study and might provide an important strategy to combat FMS-associated diseases.
Keywords: Probiotics; prebiotics; fibromyalgia syndrome; pain; depression